Salvia reuterana Extract Prevents Formation of Advanced Glycation End Products: An In Vitro Study: Antioxidant activities of extract of species of Salvia - Mohammad Ali Esmaeili,; Mohammad Reza Kanani,; Ali Sonboli, (Iranian Journal of Pharmaceutical Sciences, 2010)
In this study, we examined the antioxidant activities of methanolic extract of three endemic species of Salvia from Iran (S. lachnocalyx, S. reuterana and S. sahendica) employing various established in vitro systems including ferric reducing antioxidant power, Trolox equivalent antioxidant capacity assay and scavenging of 1,1-diphenyl-2-picrylhydrazyl radical. The results revealed that S. reuterana extract possess the highest antioxidant activity, total phenolic and flavonoid contents among these three species. Regarding the link between glycation and oxidation, we proposed that the S. reuterana extract might possess significant in vitro antiglycation activities as well. The S. reuterana extract also showed strong inhibitory effects on the production of Amadori products and advanced glycation end products from bovine serum albumin in the presence of fructose in term of protein carbonyl formation and thiol oxidation. The structural changes of bovine serum albumin (BSA) with fructose, in the presence of S. reuterana extract were evaluated by circular dichroism and fluorescence techniques. Regarding enhancing the helicity of the protein and preventing helix decrement in the secondary structure of BSA in the presence of fructose, it can be concluded that S. reuterana extract and its constituents may act as an anti-glycation agent for bovine serum albumin.